1931
DOI: 10.1103/physrev.37.1155
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Kundt's Tube Dust Figures

Abstract: An experimental study of the dust striations in a Kundt's tube has been carried out using a loud speaker, operated from a vacuum tube oscillator, as a source of sound. It is found that the positions of the vibrator for maximum agitation of the dust is different for the case in which a loud speaker is used from that obtained when a stroked rod is used. The formation and behavior of the striations is described in detail. It is found that the spacing between the striations increases with the intensity of sound, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Acoustic streaming was further studied in the context of Kundt's tubes and particle collection from the mid1800s to the early 20th century (Hutchisson & Morgan 1931); Rayleigh (1884) and Schlichting (1932) showed a stationary (or standing) acoustic wave at or near a solid boundary induces fluid motion within an adjacent boundary layer, commonly referred to as Schlichting streaming or as the Schlichting boundary layer. The layer is equivalent to the Stokes boundary layer when the acoustic wavelength is much larger than the boundary layer thickness, and is governed by viscous dissipation and weak † Email address for correspondence: james.friend@rmit.edu.au inertia that lead to periodic vortices and a steady drift velocity at the outer edge of the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic streaming was further studied in the context of Kundt's tubes and particle collection from the mid1800s to the early 20th century (Hutchisson & Morgan 1931); Rayleigh (1884) and Schlichting (1932) showed a stationary (or standing) acoustic wave at or near a solid boundary induces fluid motion within an adjacent boundary layer, commonly referred to as Schlichting streaming or as the Schlichting boundary layer. The layer is equivalent to the Stokes boundary layer when the acoustic wavelength is much larger than the boundary layer thickness, and is governed by viscous dissipation and weak † Email address for correspondence: james.friend@rmit.edu.au inertia that lead to periodic vortices and a steady drift velocity at the outer edge of the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…Even in South America, Peruvians were found to make whistling bottles as early as 500 BC for what anthropologists believe was communication and perhaps ritual ceremonies (Garrett and Star, 1977). Music as a human interpretation of sound rapidly advanced from Pythagoras' time (Hunt, 1978), and much has been made of the development of sound and acoustics as a scientific endeavor since the 18th century (Rayleigh and Lindsay, 1945;Beyer, 1998), as both ancient phenomena, such as the Chinese spouting bowl (Schufle, 1981) studied by John Tyndall and a crude predecessor of some of the atomizers described later in this review, and contemporary phenomena such as Kundt's tube (Hutchisson and Morgan, 1931) were studied and explained by leading scientists of the time. Many of the known phenomena in acoustics bear their name, with Lord Rayleigh's studies of fluid surface instabilities, human hearing and fluid jets (Nobel Foundation, 1967), Helmholtz's studies of resonant acoustic cavities, Faraday's observation of vibration-induced surface waves (Faraday, 1831;Miles, 1992), Rayleigh's acoustic streaming (Rayleigh, 1884), and the study of wave propagation in solids by Adams and Soh (2010) are five examples.…”
Section: Background a Acousticsmentioning
confidence: 99%
“…But this phenomenon is in air, where most practical applications in microfluidics are in water or a biological fluid with greater density and viscosity. Haake and Dual (2002) illustrated the typical approach to manipulating particles in fluids with ultrasound: A standing wave formation where the forces on the particles act to drive them to the nodes of the pressure field in the fluid, a phenomenon known since 1866 when Kundt found particles collecting in a pattern in a tube driven by a standing sound wave (Hutchisson and Morgan, 1931). By controlling the distribution of motion in the device, the form of collection can be significantly altered: Vainshtein et al (1996) showed how one could induce particle collection along a continuous line down the central axis of a tube instead of Kundt's discrete collections of particles in cross-sectional planes, each separated from the next by one-half the acoustic wavelength.…”
Section: Particles Colloidal Suspensions and Bubblesmentioning
confidence: 99%
“…The AS phenomenon is due to second-order nonlinear effects in the coupling between acoustics and hydrodynamics. Historically, acoustic streaming was extensively studied in relatively large fluid volumes like in Kundt's tubes excited by kHz-range acoustic forcing (Hutchisson and Morgan 1931). More recently, AS was investigated in microfluidic channels using transducers in pairs or with reflectors in order to realize a condition of resonance (Lei et al 2013;Bruus 2012).…”
Section: Introductionmentioning
confidence: 99%